Influence of surfactant on morphology of polydivinylbenzene microcapsule encapsulated octadecane - นามวงศ์, ศิริลักษณ์; มูลมั่งมี, สมพร; ไชยสัตย์, อมร; ไชยสัตย์, ปรียาภรณ์ (Progress in Applied Science and Technology, 2014)
In this research, the influence of three surfactants on the morphology of polydivinylbenzene microcapsule encapsulated octadecane (OD) prepared by microsuspension polymerization was studied. Using polyvinylalcohol (PVA), monomer droplet and polymer capsule sizes were about 1-10 μm. OD was completely enveloped with polymer shell. The obtained spherical capsule was smooth surface with a dent. In the case of sodiumdodecyl sulfate (SDS) and myristyl trimethyl ammonium bromide (TTAB), monomer droplet and polymer capsule sizes were smaller than those of PVA. The prepared capsules were half-moon liked having nonuniform polymer shell. After washing with 2-propanol, in the case of microcapsule prepared with PVA, the %loading of OD was approximately 50% and encapsulation efficiency was about 100%. In addition, the heats of melting and crystallization of OD were 193 and 182 J/g-OD, respectively, which lower than those of pure OD because of the influence of encapsulation. On the other hand, using SDS and TTAB, there is no OD peak due to incomplete encapsulation.